Synthesis, Characterization and Fungicidal Effects of some Organoborates - Akhter, Shaheen; Khanal, DP; Ullah, SS (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
Synthesis of benzoyl borate, phthasloyl borate and oxyl borate was done and characterized by infra red, ultraviolet and mass spectra. All newly synthesized and characterized organoborates were tested for their antifungal activity against pencillium that spoilt mostly celluloid materials stored in museum. All synthesized organoborates are unstable in room temperature and quickly degraded on exposure to air. Benzoyl borate found to be most active antifungal compound of the series against penicillium. The fungicidal activity increases in hydrophobicity and electron withdrawing nature of the benzene ring substituents. These compounds may be good fungicidal for the conservation of celluloid materials lying in the museum. DOI: http://dx.doi.org/10.3126/jmmihs.v1i1.9895 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(1) 2011; 1-7